The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41398-022-01969-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic DNA and RNA damage from oxidation after serotonergic treatment of unipolar depression

Abstract: Previous studies have indicated that antidepressants that inhibit the serotonin transporter reduces oxidative stress. DNA and RNA damage from oxidation is involved in aging and a range of age-related pathophysiological processes. Here, we studied the urinary excretion of markers of DNA and RNA damage from oxidation, 8-oxodG and 8-oxoGuo, respectively, in the NeuroPharm cohort of 100 drug-free patients with unipolar depression and in 856 non-psychiatric community controls. Patients were subsequently treated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The markers do not show diurnal variation (Grew et al, 2014 ) and are highly stable for 10+ years when stored at −20 degrees Celsius (Henriksen et al, 2021 ). We recently demonstrated that the storage time did not influence the marker levels in the present cohorts (Jorgensen et al, 2022 ). The exact subcellular origins of the molecules have not been completely clarified, but the cellular release of 8‐oxodG is thought to stem from enzymatic repair of DNA and/or the nucleotide pool, whereas the release of 8‐oxoGuo is thought to stem from the degradation of RNA.…”
Section: Methodsmentioning
confidence: 50%
“…The markers do not show diurnal variation (Grew et al, 2014 ) and are highly stable for 10+ years when stored at −20 degrees Celsius (Henriksen et al, 2021 ). We recently demonstrated that the storage time did not influence the marker levels in the present cohorts (Jorgensen et al, 2022 ). The exact subcellular origins of the molecules have not been completely clarified, but the cellular release of 8‐oxodG is thought to stem from enzymatic repair of DNA and/or the nucleotide pool, whereas the release of 8‐oxoGuo is thought to stem from the degradation of RNA.…”
Section: Methodsmentioning
confidence: 50%
“…Increasing data suggest that there is a signi cant elevation in 8-OH-dG levels in depression [4,28]. However, follow-up studies suggest that the increase in acute depression is reversible and returns to normal values after the resolution of depressive symptoms [20,21,29]. It should be noted that the siblings with previous episodes were euthymic at the time of inclusion in our study.…”
Section: Discussionmentioning
confidence: 78%
“…In a meta-analysis, DNA oxidation damage seem to be higher in MDD patients compared to controls [ 109 ]. Interestingly, modifications of urinary 8-oxo-7,8-dihydroguanosine (8-oxoGuo), a biomarker of RNA oxidation, were also observed in MDD [ 115 , 116 ]. Increased hippocampal RNA oxidation was also observed in a postmortem study of depressed patients [ 117 ].…”
Section: Discussionmentioning
confidence: 99%